The schemes of students' understanding through digital argumentation in online learning during pandemic COVID-19 - Marheny Lukitasari; Jeffry Handhika; Wasilatul Murtafiah; Ahmad Sukri (Intelektual Pustaka Media Utama, 2021)
The student conception needed to analyze problems and obtain effective solutions. It is also required to train students to think reflective and argumentative, so expressing student conception is necessary. This research aimed to describe the schemes of students' conception through digital arguments in online learning. This research was descriptive qualitative by uncovering students 'digital arguments and making schemes of students' understanding based on digital arguments presented in written discussions. Research Data were from electronic discussion forums, and unstructured interviews in biology and physics. The analysis results describe that digital argumentation can use to schemes students' conception.